The application of decreasing musharakah assets financing in Islamic banking - Ben Mohamed, Abdallahi; Sadique, Muhammad Abdurrahman (s.n, 2012)
This research investigates the mode of decreasing partnership (musharakah mutanaqisah) as proposed by contemporary scholars for application by Islamic banks in financing procurement of assets, as an alternative to financing based on murabahah. The research analyses different issues pertaining to this mode that are relevant to its application in asset financing by Islamic banks, with a view to assessing their shari’ah acceptability and being in line with the general principles of financing in Islamic law. The research sheds light on some aspects of shari‘ah importance related to this mode, and attempts to propose measures for enhancing the effectiveness of decreasing partnership in banking practice. Keywords: Islamic law, decreasing